Money and banking - Culbertson, J.M. (New York McGraw - Hill Book Company, 1972)
This is a textbook for the undergraduate course in money and banking. It treats the usual subjects of the course at a level suited to the student who has had only the introductory course in economics.
Includes index
osc 26/09/2017
Loans
Keywords: Banks and banking; Money